Aerodynamics of aftermarket rear spoiler - Ridhwan, Che Zake (2008)
Performance, handling, safety, and comfort of a car are significantly affected by its aerodynamic properties. Getting high power under the hood is not enough to judge the performance of the car. Aerodynamic properties must be considered for the purpose of studying the drag and stability performance of a car. In order to improve car aerodynamic drag and its stability, an aerodynamic device is needed such as rear spoiler. Rear spoiler is an aerodynamic device that functions to slow down and collect air, causing it to stagnate. This rear placing device creates an area of high pressure to replace the usual low pressure over the trunk resulting increasing stability. The objective of this study is to investigate the effects of aftermarket rear spoiler to car aerodynamics drag and stability. Several rear spoilers design is attached at rear part of base line model. Both BLM model and rear spoiler models are built in CAD software. The CAD data then, either with or without rear spoiler are analyze in CFD software to estimate the drag and lift force which is acting on the car. Force, drag and lift coefficient values will be determined in order to study their effect to drag and stability. Some limitations occurred due to the complexity of the design. From the result, rear spoiler can help to reduce drag, by creating high pressure at the back.